Naringenin Targets PI3K p85alpha to Suppress PI3K/AKT Signaling Pathway and Ameliorate Disordered MMP-9 Secretion in Cigarette Smoke Extract-Induced Alveolar Macrophages In Vitro - Weiyang Fan; Ziyan Xu; Mengli Zhong; Xiao Wu; Pan Chen; Zhen Chen; Weiwei Su; Hao Wu; Peibo Li (Cells)
Background: Naringenin has demonstrated potential therapeutic effects against cigarette smoke-induced lung injury; however, its underlying mechanisms of regulating matrix metalloproteinase-9 (MMP-9) in alveolar macrophages remain unclear. Methods: The regulatory mechanisms of naringenin in cigarette smoke extract (CSE)-induced alveolar macrophages were investigated using proteomics, and then, naringenin’s targets were further validated by Western blot, molecular docking, molecular dynamics (MD) simulations, cellular thermal shift assay (CETSA), and enzyme activity assay. Results: The proteomics revealed that the PI3K/AKT signaling pathway might play a crucial role in naringenin’s inhibition of MMP-9. Western blot analysis confirmed that naringenin significantly inhibited CSE-upregulated PI3K/AKT signaling pathway and reduced MMP-9 expression in MH-S cells. Notably, the PI3K activator 740Y-P reversed naringenin’s effects on MMP-9. Additionally, molecular docking, MD simulations, and CETSA identified PI3K p85alpha as the potential binding site for naringenin, and naringenin markedly inhibited CSE-induced PI3K activity. In in vitro experiments, naringenin inhibiting MMP-9 secretion in alveolar macrophages contributed to alleviating elastin and E-cadherin damage in alveolar epithelial cells. Furthermore, naringenin effectively suppressed CSE-induced MMP-9 secretion in primary mouse alveolar macrophages and human THP-1-differentiated macrophages. Conclusions: Our findings revealed that naringenin, a potential candidate for treating smoking-induced lung injury, directly targeted PI3K p85alpha, inhibiting PI3K activity and MMP-9 expression in CSE-induced alveolar macrophages via suppressing the PI3K/AKT signaling pathway.